The application of x-ray, computed tomography, and magnetic resonance imaging on 22 pediatric Langerhans cell histiocytosis patients with long bone involvement: A retrospective analysis. Issue 17 (April 2018) - Zhang, Xiaojun; Zhou, Jing; Chai, Xuee; Chen, Guiling; Guo, Bin; Ni, Lei; Wu, Peng
Abstract : Abstract: The studies focusing on x-ray, computed tomography (CT), and magnetic resonance imaging (MRI) in pediatric Langerhans cell histiocytosis (LCH) patients were still rare. Therefore, we aimed to evaluate the application of x-ray, CT, and MRI in pediatric LCH patients with long bone involvement. Total 22 pediatric LCH patients were included in this study. The diagnosis of LCH was confirmed by pathological examination. All patients were followed up for 3 years. X-ray, CT, or MRI was performed and the results were recorded for further analyses. Among 22 pediatric patients, x-ray (n = 20), CT (n = 18), or MRI (n = 12) were used to scan the lesion on long bones affected by LCH. Femurs (n = 13, 38.24%), tibia (n = 11, 32.35%), humerus (n = 5, 14.71%), and radius (n = 4, 11.76%) were the most frequently affected anatomic sites. Ovoid or round radiolucent lesions, aggressive periosteal reaction, and swelling of surrounding soft tissues were characteristic image of long bones on x-ray, CT, and MRI in pediatric LCH. Femurs, tibia, humerus, and radius were the most commonly affected long bones of pediatric LCH. The application of x-ray, CT, and MRI on long bones could help with the diagnosis of pediatric LCH.